The Politics of Marketising Asia
XX, 313 p.
Keywords: Economic growth continues to transform the economic and political landscape of Asia. Equally the policies now being adopted to promote private sector participation, re-structure state entities, and reduce the presence of the state in the provision of public goods and services, are tied to fundamental transformations in Asia's state-society relations. The global cast of contributors present a timely analysis of the impact of neo-liberalism on Asia's developmental policies and the organisation of Asian states and markets. Ironically, the "developmental state" that has historically driven Asia's rapid economic transformation is now threatened by an increasingly dominant neoliberal agenda that aims to roll back the state in the name of market fundamentalism.